PENGEMBANGAN SISTEM PAKAR DIAGNOSA HAMA DAN PENYAKIT TANAMAN PADI MENGGUNAKAN METODE CERTAINTY FACTOR BERBANTUAN METODE KUANTIFIKASI PERTANYAAN - Gede Mahardika (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2012)
LPHP (Laboratorium Pengamatan Hama dan Penyakit) Tangguwisia is a laboratory unit that supports the activities of Balai Proteksi Tanaman Pangan dan Hortikultura Bali. To overcome the limitation of the numbers of agricultural experts in LPHP Tangguwisia, the solution is by developing a system that has the same abilities as an agricultural expert. This system will acquire the expertise or knowledge of an expert into a knowledge base system. In this study there will be developed a Diagnosis Expert System of Rice Plant’s Pests and Diseases in a desktop-based using the Certainty Factor method assisted by quantification of questions method. Certainty Factor is a method of probability that is used to determine the results of diagnostics within this expert system, whereas the quantification of questions is a method used for determining the value of certainty of every data symptom owned by the users of the system. Test results shows that the expert system is able to diagnose pests and diseases of rice plants based on the income of data symptoms done by the system’s users. In addition, the expert system is also able to provide a solution or prevention techniques associated with pests or diseases as the result of the diagnosis.